The regulation of the sexual harassment in the workplace by the collective bargaining in Portugal - Marques Alves, P. (Conference Long-term Global Perspectives on Preventing Sexual Harassment in the Workplace: Policy, Practice and Strategies, 2020)
Probably as old as wage work and reaching successive generations of women, sexual harassment in the workplace has assumed international relevance only since the 1980s. Portugal seems to have been one of the first countries where it was tackled when at the end of that decade the CITE - Commission for Equality in Labour and Employment commissioned a study which found that 25.5% of the women surveyed had already been victims of harassment by colleagues; 13.6% by their superiors and 7% by clients or suppliers (Amâncio and Lima, 1994). Based on this study, several initiatives of CITE, feminist associations or trade union confederations were carried out over the following decades, namely workshops, researches, publication of leaflets or scientific articles, etc.. The most recent study (Torres et al., 2015) concluded that 12.6% of the active population has already suffered at least once during their working life a form of sexual harassment in the workplace. However, this may only be the tip of the iceberg. Although since the Constitution of 1976 there has been a legal framework for the issue under its provisions on equality, dignity and the prohibition of discriminatory acts, the effective regulation of all forms of harassment has only very recently been implemented in the Portuguese legal system. This was the case with the 2003 Labour Code, which applies to the private sector; with the 2014 General Labour Law in Public Service, which applies to the public administration; and with the new Penal Code of 2015. The same applies to collective bargaining. Being an attack to the dignity of workers, it is up to trade unions to take the sexual harassment in the workplace into the agenda and act to prevent it from occurring or, if it does, to participate in the definition of mechanisms in order to sanction this behaviour. Collective bargaining is a privileged instrument of making this prevention effective and of enabling the existence of working environments free from sexual harassment. Effectively, in the late nineteenth century, Sydney and Beatrice Webb considered that it strongly contributed to the creation of a "democratic industrial order" based on justice. Flanders later stressed its relevance as a factor in overcoming the individualization of labour relations and as a source of definition of labour and social rights, and Clegg emphasized that it implies the joint definition of substantive norms, with unions succeeding in influencing working conditions in a way favourable to workers. This communication is based on an extensive analysis of the collective agreements published between 2015 and 2018. It is concluded by the almost total invisibility of the regulation of this matter, since there are very few agreements that address it and, when they do so, the norms are basically limited to copy and paste what is stipulated in the legislation. There are, however, provisions that stand out and that should be highlighted as examples of good practices, such as the definition of the compensation amounts to be paid to victims or the trade union participation in the process.